(untitled) (Journal of Science Foundation, 2019)
Background: Carica papaya is very useful vegetables for daily living. Objective: The purpose of the present study was to compare the anti-inflammatory effect of ethanolic extract of Carica papaya leaves and indomethacin in carrageenan induced rat paw edema animal model. Methodology: This was an animal study carried out in the Department of Pharmacology at Dhaka Medical College, Dhaka, Bangladesh during the period from July 2014 to June 2015 for a period of one (01) year. The leaves of Carica Papaya collected from Botanical garden, Mirpur, Dhaka, Bangladesh. The animals were divided into four groups. Inflammation was produced by injecting 0.1 ml of 1% carrageenan solution in normal saline in all experimental animals. Group I were served as control that received normal saline. Group II were received ethanolic extract of Carica Papaya. Group III were received ethanolic extract of Carica Papaya leaves. Group IV were received indomethacin. Result: The experiment was carried out on 48 Long Evan Norwegian rats. Rats were divided in 4 groups of six animals each. The mean initial antero-posterior diameter of rat’s paw of group I, II, III and IV were 3.83±0.04, 2.12±0.02, 1.74±0.01 and 1.60±0.03 respectively. The inhibition of edema formation were 44.64%, 54.57% and 58.22% in group II, III and IV respectively. Conclusion: In conclusion the Carica papaya leaves has anti-inflammatory effect Journal of Science Foundation 2018;16(2):49-53